A purr-fect pumpkin - Bardhan-Quallen, Sudipta (Bardhan-Quallen, Sudipta. Purrmaids, 2022)
In Kittentail Cove, Paw-loween is a super fun holiday! Shelly, Coral, and Angel can't wait to decorate jelly-o-lanterns, dress up in costumes, and go to the Paw-loween festival! But Coral is a little nervous about the Haunted House. Can this scaredy cat learn to be brave so she can see her purr-fect pumpkin on display in the house? Maybe with a little help from her friends!